Neonatal Jaundice History as a Risk Factor for Speech Delay in Children Aged 0–6 Years - Sanjaya, Ayling; Prasetyo, Mohammad Yudhi; Santoso, Anna Lewi (Humanistic Network for Science and Technology (HNST), 2025)
Untreated neonatal jaundice can result in neurological complications, including speech delay. This study aimed to analyze the association between a history of neonatal jaundice and speech delay in children aged 0–6 years at a Private Clinic in Malang. This research applied a case-control design with a total sample of 60 children, including 30 children with speech delay and 30 children with normal speech development. Jaundice history data were collected through parent questionnaires, while speech development was assessed using the Developmental Pre-Screening Questionnaire. Data analysis used the Chi-Square test with a significance level of 0.05. The results showed no statistically significant relationship between neonatal jaundice and speech delay (p = 0.103). However, the Odds Ratio of 2.875 indicated that children with a history of neonatal jaundice were at a higher risk of experiencing speech delay. In conclusion, although no statistically significant association was found, a history of neonatal jaundice may serve as a risk factor for speech delay in children aged 0–6 years. Therefore, early developmental monitoring is strongly recommended for children with such a history. Keywords: bilirubin; early childhood; neonatal jaundice; speech delay